KETERAMPILAN MENGOLAH TANAMAN OBAT TRADISIONAL UNTUK PENYAKIT ANAK PADA KOMUNITAS REMAJA BALI : SEBUAH KAJIAN EKOLINGUISTIK - Rasna, I Wayan; Binawati, W.S. (Bumi Lestari; Vol 14 No 1 (2014), 2014)
This study aims at knowing: 1) the skill of the young generation in cultivating traditional medical plantation for children’s disease, 2) the implication of the first goal towards ecolinguistics. The setting of the study was in Bali province, consisting of 8 regencies and one city government, with the total of samples of young generation 360 and the sample of healers 45 individuals. The samples were determined by using purposive quota sampling technique. The data about the skill were collected observation, and the data about the implication the first goal were collected through interview. The result of the study shows that: 1) the skill of the young generation in cultivating traditional medical plantation was totally 58.5%, and partially there were young generations who could cultivate traditional medical plantation, such as Karangasem 73.12 (good), Klungkung 70.50 (good), and Bangli 71.36 (good), 2) the implication of   the first goal to eco-linguistics is that the young generations having better ability in cultivating medical plantation are more familiar with the medical plantation terms, though the physical representation of the plant is not definitely known. In this case, the skill in cultivating traditional plantation and the synergy among the related components are needed to increase for the maintenance of the medical plantation terms and environmental preservation.
Keywords: skill, medical plantation, eco-linguistics